Arguments for a neuroorthopaedic strategy in upper limb arthrogryposis - Bahm, Jörg (Journal of Brachial Plexus and Peripheral Nerve Injury, 2013)
We present two children with a diagnosis of upper limb arthrogryposis and report on findings about brachial plexus exploration and a nerve transfer procedure to reanimate elbow flexion. Although the etiology of arthrogryposis multiplex congenita remains unknown and multifactorial, it can be worthful to explore the brachial plexus in the affected upper limb and to perform selective motor nerve transfers on morphologically well developed but not sufficiently innervated target muscles, like the biceps brachialis, brachialis, deltoid and supra-/infraspinatus muscles. This strategy may reduce the necessity of later muscle transfers and improves the overall functional status of the affected limb(s).
Keywords: Arthrogryposis; Upper limb; Nerve transfer; Brachial plexus